Learning by observation in children with autism spectrum disorder. Issue 11 (August 2014) - Foti, F.; Mazzone, L.; Menghini, D.; De Peppo, L.; Federico, F.; Postorino, V.; Baumgartner, E.; Valeri, G.; Petrosini, L.; Vicari, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Observing another person performing a complex action accelerates the observer's acquisition of the same action and limits the time-consuming process of learning by trial and error. Learning by observation requires specific skills such as attending, imitating and understanding contingencies. Individuals with autism spectrum disorder (ASD) exhibit deficits in these skills. Method The performance of 20 ASD children was compared with that of a group of typically developing (TD) children matched for chronological age (CA), IQ and gender on tasks of learning of a visuomotor sequence by observation or by trial and error. Acquiring the correct sequence involved three phases: a detection phase (DP), in which participants discovered the correct sequence and learned how to perform the task; an exercise phase (EP), in which they reproduced the sequence until performance was error free; and an automatization phase (AP), in which by repeating the error-free sequence they became accurate and speedy. Results In the DP, ASD children were impaired in detecting a sequence by trial and error only when the task was proposed as first, whereas they were as efficient as TD children in detecting a sequence by observation. In the EP, ASD children were as efficient as TD children. In the AP, ASD children were impaired in automatizing the sequence. Although the positive effect of learning by observation was evident, ASD children made a high number of imitative errors, indicating marked tendencies to hyperimitate. Conclusions These findings demonstrate the imitative abilities of ASD children although the presence of imitative errors indicates an impairment in the control of imitative behaviours.